Vulnerability and Poverty Transitions Among Rural Households in South West Nigeria (2011)
Successive governments in Nigeria have implemented poverty alleviation programmes and strategies without commensurate reduction in poverty. The near failure of these programmes and strategies has been associated with improper diagnosis of poverty as a static rather than dynamic concept. Poverty dynamics enables a better appreciation of the extent of poverty over time by distinguishing between households exiting and entering into poverty, those never poor and the persistently poor. The dynamics of and vulnerability to poverty in rural Southwest Nigeria (SWN) were therefore investigated. Primary data were collected from a two-wave panel survey (harvesting and lean periods) employing a multi-stage sampling technique. The first stage was a random selection of Oyo and Osun states. Thereafter, was the random selection of three Local Government Areas (LGAs) from each state. Ten rural Enumeration Areas (EAs) were randomly selected from each LGA and ten households were systematically selected from each EA. In all, 600 households were interviewed in the Harvesting Period (HAP) out of which 582 could be tracked in the Lean Period (LEP) which constituted the sample size. The sample was weighted using the inverse of the overall selection probabilities to make it representative of the region. Information was collected on socioeconomic and demographic characteristics, monthly consumption expenditure as well as economic infrastructure available in the respondents’ communities. Data were analysed using descriptive statistics, Foster, Greer and Thorbecke poverty measure, 3- Stage Feasible Generalized Least Squares, Tobit, Probit and Multinomial Logit regression methods. A higher proportion of the households (79.6%) were headed by males. The mean age and household size of the respondents were 50.8 ± 15.3 years and 5.0 ± 3.3 respectively. The mean per capita household consumption expenditure at HAP was N4970.36 ± N3274.25, while that of LEP was N6140.43 ± N5113.94 with poverty lines of N3313.57 and N4093.21 respectively. The incidence of poverty was 35.0% for HAP and 43.6% for LEP. At the standard vulnerability threshold of 0.5, 55.7% of rural households in SWN were vulnerable to poverty. A unit increase in household size and dependency ratio aggravated vulnerability by 0.05 and 1.28, while attainment of secondary and tertiary education reduced (p<0.01) vulnerability by 0.14 and 0.23 respectively. Vulnerability also translated into significantly (p<0.01) higher poverty by increasing the ex-post probability of becoming poor by 0.34. Household poverty transitions revealed that 49.5% of the households were never poor, 28.2% were chronically poor, while 22.3% were transiently poor. However, of the transient poor, while 6.8 percent exited poverty, 15.5 percent moved into poverty. Vulnerability aggravated both chronic and transient poverty by impacting on the odds of being chronically poor and moving into poverty by 10.05 and 1.80, respectively (p<0.05). The poor in Southwest Nigeria were a heterogeneous group consisting of the transient and chronic poor. Vulnerability trapped poor households in poverty while propelling the non-poor into it. Poverty dynamics and vulnerability underscored the centrality of effective poverty reduction tools in Southwest Nigeria